Functional Insights Into the Role of gppA in (p)ppGpp Metabolism of Vibrio cholerae - Rakshit, Dipayan; Dasgupta, Shreya; Das, Bhabatosh; Bhadra, Rupak K. (Frontiers in Microbiology, 2020)
The stringent response, an adaptive response to nutrient limitation and exposure to xenobiotics in bacteria, is mediated by two intracellular signalling molecules, pppGpp and ppGpp, together called (p)ppGpp. The cellular level of (p)ppGpp in bacterial cells is controlled by the Rel/Spo family of proteins. In the cholera pathogen Vibrio cholerae (p)ppGpp metabolism is regulated by the products of at least three genes relA, spoT and relV. In this study, we identify and characterize the function of the guanosine-5’-triphosphate 3’-diphosphate pyrophosphatase A (GppA) encoding gene gppA of V. cholerae. Genomic analysis indicates that the gppA locus is conserved in vibrios and organized as a bicistronic operon along with the rhlB gene. We engineered the genome of V. cholerae to develop different mutants devoid of GppA and/or other phosphate metabolic enzymes. Our findings indicate that in V. cholerae GppA plays an important role in the conversion of pppGpp to ppGpp during amino acid deprivation but not during glucose starvation. Quantitative analyses of the gppA transcript level reveal its differential expression pattern at different growth phases and starvation conditions. It has been observed that the GppA deficiency during amino acid starvation condition could be complemented by overexpressing the exopolyphosphatase coding gene ppx of V. cholerae. By deletion analysis we further demonstrate that the amino and carboxy terminal sequences flanking the Ppx-GppA motif of the GppA protein of V. cholerae are also important for its enzymatic function.